Relationship between physical activity and sleep among university students in Singapore - Yap, Jeter (2019)
This study aims to establish a relationship between physical activity (PA) and sleep of university students in Singapore, to promote an active lifestyle at the tertiary level and ultimately cope with the ill-effects of sleep deprivation and physical inactivity that has been prevalent in Singapore. 100 Sport Science and Management (SSM) students participated in this study. Two questionnaires were administered – International Physical Activity Questionnaire-Short Form (IPAQ-SF) and Pittsburgh Sleep Quality Index (PSQI). Data collected were tested for correlation and relationship between sleep variables and PA. Pearson’s correlation coefficient indicated a negative correlation between PA and PSQI Score, suggesting increased levels of PA led to better sleep. However, this result was weak and statistically insignificant (p > 0.05). Male had significantly lower mean PSQI Score (i.e. better sleep) than female student. Students categorized as HIGH-PA obtained a lower mean PSQI Score (i.e. better sleep) than MOD-PA students. Lower mean PSQI Score (i.e. better sleep) corresponded to groups with higher levels of PA. However, the notion that PA leads to better sleep cannot be ascertained as the result was insignificant. The lack of statistical significance on correlation could be caused by the small amount of LOW-PA sample (n=1). This would have naturally skewed the results towards higher levels of PA, hence causing a diminished relationship with sleep quality. Thus, the relationship between PA and sleep of university students in Singapore is inconclusive, and future research should look to increase the sample size to include a substantial number of LOW-PA group.